(untitled) (Bioagro, 2020)
The biocontrol effect of five plant growth promoting microorganisms (PGPM): Trichoderma koningii strain Vp, Penicillium rugulosum strain IR, Penicillium sp. strain 20, Enterobacter sp. strain CR, and Bacillus megaterium strain 24B2 was evaluated in laboratory and greenhouse conditions on two isolates of the pathogen Alternaria alternate identified as 475 and 485, during the cultivation of tomato plants (Solanum lycopersicum L.). For this, it was stated the following steps: 1) antagonism and germination in laboratory conditions, 2) plantlet growth in propagation trays, and 3) plant growth in pots using a natural soil. The biocontrol effect of these PGPM showed that T. koningiiVp induced the most antagonistic effect since the beginning until 72 hours of measuring on the two isolates of A. alternata, and also the germination percentage of seeds was increased significantly (P≤0.05).Likewise, at greenhouse conditions, itwas found that plantlets inoculatedwith both PGPM, T. koningii Vp and P. rugulosum IR, showed the lowest percentage of infection for the two pathogen isolates. In the pot experiment, the percentage of leaf spot infection on the plants inoculated with T. koningii Vp showed a significant (P≤0.05) biocontrol over pathogens, followed by those inoculated with Enterobacter sp. strain CR. It is concluded that PGPR evaluated over different experiments showed variability in their biocontrol competence and plant growth promotion of tomato, related to the pathogen A. alternate and the plant growth state.